The Flickering Philosophy of Impressionism: a Literary-Critical Perspective - Golod, Roman (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses the attitudinal and philosophical premises of impressionism as a literary movement. The author explores the causes of difficulties associated with identifying literary works as impressionistic. The paper then explores the reasons for the shift in the attitudinal and philosophical conceptualization of impressionism from rationalist positivism to irrationalist trends in the “philosophy of life”. The conclusion discusses the impact of the philosophical basis of impressionism on the character of its poetics.